Cleft Lip – A Comprehensive Review - Shkoukani, Mahdi A.; Chen, Michael; Vong, Angela (Frontiers in Pediatrics, 2013)
Inauguration article/Review, I didn't put in an abstract because I noted similar articles in the journal didn't have an abstract. if one is needed then will do that.